Tensile Response of As-Cast CoCrFeNi and CoCrFeMnNi High-Entropy Alloys - Tu-Ngoc Lam; Mao-Yuan Luo; Takuro Kawasaki; Stefanus Harjo; Jayant Jain; Soo-Yeol Lee; An-Chou Yeh; E-Wen Huang (Crystals, 2022)
In this research, we systematically investigated equiatomic CoCrFeNi and CoCrFeMnNi high-entropy alloys (HEAs). Both of these HEA systems are single-phase, face-centered-cubic (FCC) structures. Specifically, we examined the tensile response in as-cast quaternary CoCrFeNi and quinary CoCrFeMnNi HEAs at room temperature. Compared to CoCrFeNi HEA, the elongation of CoCrFeMnNi HEA was 14% lower, but the yield strength and ultimate tensile strength were increased by 17% and 6%, respectively. The direct real-time evolution of structural defects during uniaxial straining was acquired via in situ neutron-diffraction measurements. The dominant microstructures underlying plastic deformation mechanisms at each deformation stage in as-cast CoCrFeNi and CoCrFeMnNi HEAs were revealed using the Convolutional Multiple Whole Profile (CMWP) software for peak-profile fitting. The possible mechanisms are reported.